Technological, pedagogical, and content knowledge among mathematics teachers: Difference of teaching experience and certification status - Badjeber, Rafiq; Yulia, Yulia; Mijra, Mijra; Winda, Winda (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Teachers continue to face challenges in applying Technological, Pedagogical, and Content Knowledge (TPACK) in classroom settings. Many mathematics teachers, in particular, lack adequate preparation and mastery of the three core components of TPACK.Aim: This study aims to investigate and analyze differences in TPACK proficiency among mathematics teachers based on their teaching experience and certification status.Method: Adopting a mixed-method approach with a sequential explanatory design, the study involved 65 Islamic Junior and Senior High School mathematics teachers in Palu City, selected through proportionate stratified random sampling. Additionally, four teachers were interviewed to gain deeper insights. The instruments used included TPACK questionnaires and structured interview guidelines.Results: The findings revealed no significant differences in TPACK proficiency between certified and non-certified mathematics teachers. While teachers demonstrated a solid understanding of content and appropriate teaching methods, they seldom incorporated technology into their instruction. Furthermore, teaching experience showed no substantial impact on TPACK proficiency. Junior teachers were observed to have better familiarity with technology, while senior teachers exhibited greater adaptability in managing diverse classroom situations.Conclusion: Certification status and teaching experience do not significantly influence TPACK proficiency among mathematics teachers. The primary barrier to integrating technology lies in limited access to adequate facilities. Continued professional development initiatives are essential to enhance teachers' technological competencies and their integration into classroom practices.